Berber Clitic Doubling and Syntactic Extraction - Guerssel, Mohamed (Revue québécoise de linguistique, 1995)
ABSTRACTThe aim of this paper is twofold. First it is argued that the overt realization of lexical subjects in Berber is an instance of clitic doubling. The markers that have traditionally been considered to be merely agreement markers are to be treated as clitics. Second, and contrary to standard assumptions, it is shown that extraction out of clitic doubling is universally possible provided a default clitic is available. Evidence in favor of the view that syntactic extraction out of doubling is rooted in a proper characterization of agreement comes from a comparison of the Berber dialects that exhibit clitic doubling and those that do not. The two dialect types contrast exactly as expected within the approach advocated.